Complete amino acid sequence of chicken cartilage link protein deduced from cDNA clones. - Deák, F (1986)
cDNA clones coding for chicken cartilage link protein were isolated and sequenced. The DNA sequence for the entire core polypeptide of the mature link protein and the predicted signal peptide consists of 1065 nucleotides. The deduced primary translation product (355 amino acids) has a molecular mass of 40.7 kDa; the calculated molecular mass of the mature link protein core polypeptide (340 amino acids) is 39.06 kDa. The DNA sequence contains two tandemly arranged repeat sequences that may code for repeated functional domains of link protein involved in binding to hyaluronic acid. The mRNAs for chicken link protein are 6.0, 5.8, and 3.0 kilobase pairs, and the difference between the sizes of the RNA species lies in the 3' untranslated region.